Ability of Surgical Residents to Impact Patient Tobacco Use in the Perioperative Setting. Issue 5 (September 2016) - Brajtbord, Jonathan S.; Odisho, Anobel Y.; Meng, Maxwell V.; Hampson, Lindsay A.
Abstract : Introduction: : Tobacco use significantly impacts patient morbidity and mortality, and is particularly important to the surgical community as it has a negative impact on surgical recovery. Despite its relevance, most surgeons do not engage in smoking cessation counseling. Methods: : As part of the UCSF Medical Center quality improvement program, urology residents designed and led an initiative targeting urological patients undergoing surgery at UCSF between August 2013 and July 2014. Our primary objectives were to 1) elicit the smoking status of at least 80% of perioperative patients who stayed at least 1 night in the hospital and 2) obtain an inpatient smoking cessation consultation for patients who were active tobacco users. Results: : A total of 934 patients were assessed, of whom 8.5% were current tobacco users, 37% were past users and 55% had never used tobacco. Current smokers were more likely to be younger and female, and less likely to have a cancer diagnosis compared to past or never smokers (all p ≤0.001). The rate of tobacco status assessment improved significantly throughout the quality improvement period, at 59.0% in quarter 1, 85.5% in quarter 2, 92.9% in quarter 3 and 94.4% by quarter 4. Patients who underwent smoking cessation consults were more likely to be prescribed nicotine replacement therapy during their hospital stay and upon discharge home. Conclusions: : Through our quality initiative program we demonstrated a fast, feasible and easily implemented approach to identify smokers, and obtain smoking cessation counseling and treatment. This practical approach represents a significant opportunity to effect change in smoking behavior at a teachable moment.